A Look Upstream: Electricity Market Restructuring, Risk, Procurement Contracts and Efficiency - Corrado Di Maria; Ian A. Lange; Emiliya Lazarova (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper analyzes theoretically and empirically how upstream markets are affected by deregulation downstream. Deregulation tends to increase the level of uncertainty in the upstream market. Our theoretical analysis predicts that deregulated firms respond to this increase in uncertainty by writing more rigid contracts with their suppliers. Using the restructuring of the electricity market in the U.S. as our case study, we find support for our theoretical predictions. Furthermore, we investigate the impact this change in procurement contracts has on efficiency. Focusing on coal mines, we find that those selling coal to plants in restructured markets are significantly more productive than their counterparts working with regulated plants. On the other hand, we also find that transaction costs may have increased as a consequence of deregulation.
Keywords: L14; L51; Q31; Q48; 330; energy policy; electricity market restructuring; deregulation; procurement contracts; risk; efficiency